Cross cultural web design interface - Jano, Zanariah (Penerbit UTeM Press, 2025)
Does standardisation or localisation exist in the interactivity dimension in university websites in terms of human to content, human to marketer and human to human category? Does standardisation or localisation exist in the usability dimension in university websites in terms of organisation and graphical design? How does cultural dimension portray for interactivity and usability dimensions in university websites? Standardisation, that is adherence to standard guidelines, implies that web designs (in terms of usability and interactivity) are culturally neutral and deviations from the guidelines, or localisation, implies that web designs are culturally sensitive. Overall, a mix of standardisation and localisation pertaining to interactivity and usability may exist in university websites of Malaysia and Australia. The intricate interplay of these three elements of culture forms the bases of website design of universities. This book, hence, is beneficial to guide students, web designers and web policy makers in understanding the cultural preferences and sensitivities of cultures for internationalization purposes.